2020
DOI: 10.4274/tjod.galenos.2020.38924
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy worsens the morbidity of COVID-19 and this effect becomes more prominent as pregnancy advances

Abstract: Amaç: İn vitro fertilizasyon (İVF) ve embriyonik manipülasyonlar yoluyla gebe kalan kadınlarda hormon kullanımı, pulmoner hipertansiyon olasılığı da dahil olmak üzere yenidoğanların sağlığıyla ilgili endişeleri artırmıştır. Bu nedenle bu çalışma, term İVF yenidoğanlarında pulmoner arter basıncını değerlendirmeyi amaçlamıştır. Gereç ve Yöntemler: Bu prospektif kesitsel çalışma Mart 2013 ile Ekim 2017 arasında gerçekleştirilmiştir ve 160 İVF yenidoğanı (grup 1) 160 doğal yolla olan yenidoğanla (grup 2) karşılaşt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 13 publications
3
30
0
1
Order By: Relevance
“…In the US, ~5–9% of women with COVID-19 were identified to be pregnant [ 33 , 44 ]. Tug et al found more severe illness among pregnancies after 20 weeks gestational age [ 42 ].…”
Section: Maternal Infection With Sars-cov-2mentioning
confidence: 99%
See 3 more Smart Citations
“…In the US, ~5–9% of women with COVID-19 were identified to be pregnant [ 33 , 44 ]. Tug et al found more severe illness among pregnancies after 20 weeks gestational age [ 42 ].…”
Section: Maternal Infection With Sars-cov-2mentioning
confidence: 99%
“…Some complications may depend on the nature of the symptomatic and asymptomatic state [ 56 ]. Preterm delivery is relatively common, but the frequency has been considerably influenced by concerns for the pregnancy and hence by iatrogenic intervention [ 2 , 13 , 23 , 29 – 31 , 34 , 35 , 37 , 39 – 42 , 46 , 55 , 56 , 59 – 61 , 66 , 68 , 77 , 83 , 90 , 94 , 95 , 101 – 110 ]. Overall, the preterm delivery rate generally approaches 14–37%, but the frequency is as high as 75% when the maternal illness is severe.…”
Section: Maternal Infection With Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“… 4 Pregnancy exacerbates the morbidity of COVID-19, with the effect potentiating as the pregnancy nears term. 4 , 6 , 7 Pregnancy increases the probability of hospital admission and intensive care. 6 , 8 There is, however, no difference in the risk of dying from COVID-19 between pregnant and non-pregnant women.…”
Section: Introductionmentioning
confidence: 99%